Lichens as Biomonitors of Air Pollutants Deposition: Strategically Important Element Pollution - Topal, E.ışıl Arslan; Topal, Murat; Öbek, Erdal; Aslan, Ali (My University, 2023)
Investigation of various species of lichen as biomonitors of air pollutants deposition and evaluation of element pollution were aimed. Maximum accumulation was 43.9±2.1 mg/kg in X. somloensis. Strontium in lichen species was quite high. Percentages of strontium for L.pulmonaria, C.furcata, U.longissima, X.somloensis, and F.caperata were between 58% and 78% indicating the efficient accumulation of strontium. Lichens were also accumulated strategically important elements. Maximum contamination factors in lichens were for strontium and tantalum. Maximum contamination factors of hafnium, niobium, lithium, gallium, and bismuth were for L. pulmonaria while maximum contamination factors of strontium, yttrium, scandium, and cerium were for X.somloensis. Maximum contamination factor of tantalum was for F.caperata. Enrichment factors for L.pulmonaria, C.furcata, and F.caperata were higher than 10, only for bismuth while lower than 10 for U.longissima. Enrichment factors for X.somloensis were higher than 10. Pollution load indexes for L.pulmonaria and U.longissima were higher than 1. Presence of strategically important elements in lichens showed that lichen species can be used as biomonitors of air pollutants.
Keywords: Environment; Accumulation; Lichen; Biomonitor; Elements; Pollutant